Analisis karakteristik kinerja dan tingkat pelayanan pada ruas jalan dengan bukaan median - Kunna, A Sarwono Suhar; Said, Lambang Basri; Maryam, St (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the effect of U-Turn facilities on traffic performance on Makassar Perintis Kemerdekaan Road, with a focus on three study points, namely KM 8+327 (in front of PO Bintang Marwah Bus), KM 10+467 (in front of Yonkav TNI Dormitory), and KM 10+910 (in front of Cokroaminoto Campus Makassar). The method used in this research is quantitative analysis based on the Indonesian Road Capacity Manual (MKJI, 1997). Data were collected through traffic surveys for three days during peak hours (07:00-09:00, 11:00-13:00, and 15:00-18:00), including vehicle volume, travel time, vehicle speed, queue ratio, road capacity, and degree of saturation. The results showed that the presence of U-Turns on the Makassar Perintis Kemerdekaan Road Section has a significant impact on increasing traffic delays and decreasing the level of road service. High vehicle volumes, especially during peak hours, cause long queues at U-Turn locations, with degree of saturation (DS) values approaching or exceeding the threshold suggested by MKJI. In addition, it was found that the presence of